Bridging the Gap: Implementing cardiac rehabilitation programmes in pakistan’s healthcare system - Hammad Najam; Muhammad Furqan Hassan; Zara Khalid; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2025)
Cardiac rehabilitation (CR) is a secondary prevention programme aimed at reducing the mortality and frequency of recurrent cardiac events and contributes to improvement in quality of life of the patients suffering from cardiovascular diseases (CVD). While the healthcare system around the world has revolutionized, provision of CR services is still lacking in its implementation. According to statistics, < 54% of the countries actually provide CR and this percentage drops at an alarming rate of about 8% and 28% in low income and lower-middle income countries (LICs/LMICs) respectively, even though the need of this programme has increased exponentially. Pakistan is one of the lower-middle income countries facing many challenges in implementing successful healthcare programmes. One such field which is neglected and often overlooked is cardiac rehabilitation. Establishing and promoting CR programmes in low-middle income countries is crucial as it can alleviate the financial strain of prolonged hospital stays and help in prevention from dependency on families. This review highlights the dilemma regarding lack of CR programmes in Pakistan, as well as factors affecting the utilization and applicability of this programme. Keywords: Cardiac rehabilitation, cardiovascular diseases, exercise training, primary prevention, secondary prevention.